Anticancer Herbal Drugs And Their Improvement Through Novel Drug Delivery Approaches (Applied Biological Research, 2013)
Cancer is one of the most devastating diseases that involves various cellular and  genetic alternations and globally is 2nd leading cause of death in humans.  Alternative medicines and their by-products provide a positive hope to manage  cancer. However, non-specific bio-distribution and targeting, less water  solubility, poor oral bio-availability and low therapeutic efficacy limit the  pharmacological properties of conventional anti-cancer herbal drugs. In this  review an attempt has been made to discuss about the mechanism and  therapeutic efficacy of twenty different anti-cancerous herbal drugs with focus  on their best utility. Different techniques of novel drug delivery systems (NDDS)  like nano-particles, phyto-complex, liposome, ethosome, nano-emulsion and  microsphere have been discussed as potential tools to remove various constraints  associated with these herbal drugs. Various important issues related with novel  drug carriers like their generalized mode of action, their potential advantages  over conventional drugs, future opportunities, technological challenges and possible steps to patch up the existing gaps have been discussed.
Keywords: Cancer; herbal drugs; novel drug delivery approaches